2018
DOI: 10.1002/jia2.25144
|View full text |Cite
|
Sign up to set email alerts
|

Systemic DPP4 activity is reduced during primary HIV‐1 infection and is associated with intestinal RORC+CD4+ cell levels: a surrogate marker candidate of HIV‐induced intestinal damage

Abstract: IntroductionCombined anti‐retroviral therapy (cART) transformed HIV‐1 from a deadly disease into a chronic infection, but does not cure HIV infection. It also does not fully restore HIV‐induced gut damage unless administered extremely early after infection. Additional biomarkers are needed to evaluate the capacity of therapies aimed at HIV remission/cure to restore HIV‐induced intestinal immune damage and limit chronic inflammation. Herein, we aimed to identify a systemic surrogate marker whose levels would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…These distinct NK cell tissue distributions were associated with CXCR3 expression, supporting its role as an inflammatory tissue homing marker for NK cells. The higher levels of the CXCR3 ligand (IP-10) in the intestine of the SIVmac-infected macaques as compared with those of the SIVagm-infected AGMs (75,76) might explain in part, together with previously reported upregulations of other receptors such as α 4 β 7 , the higher levels of NK cells in the intestine of the SIVmac-infected macaques as compared with the natural host. The fact that NK cells seem to be redirected to the intestine in SIVmac infection raises the question of their inefficient activity against the cells replicating the virus in the gut.…”
Section: Discussionmentioning
confidence: 84%
“…These distinct NK cell tissue distributions were associated with CXCR3 expression, supporting its role as an inflammatory tissue homing marker for NK cells. The higher levels of the CXCR3 ligand (IP-10) in the intestine of the SIVmac-infected macaques as compared with those of the SIVagm-infected AGMs (75,76) might explain in part, together with previously reported upregulations of other receptors such as α 4 β 7 , the higher levels of NK cells in the intestine of the SIVmac-infected macaques as compared with the natural host. The fact that NK cells seem to be redirected to the intestine in SIVmac infection raises the question of their inefficient activity against the cells replicating the virus in the gut.…”
Section: Discussionmentioning
confidence: 84%
“…Although sDPP4 directly induces inflammation in cells and animals 11,15,53 , whether circulating sDPP4 levels reflect the extent of localised or tissue inflammation is unclear. Levels of sDPP4 were reduced in humans with acute HIV infection and did not change with prolonged antiretroviral therapy 54 . In contrast, multiple studies demonstrated elevated levels of DPP4 activity and sDPP4 in subjects with obesity and/or T2D 11,15,39 , associated in some analyses with increased sDPP4 expression in circulating T cells 39 sDPP4 and liver enzymes in subjects with T2D, however levels of sDPP4 also decreased in the control group independent of changes in liver enzymes 55 .…”
Section: Discussionmentioning
confidence: 88%
“…Notably, levels of the soluble form, sDDP4, were decreased in primary and suppressed HIV-1 infection. Further, IL-21 treatment in a nonhuman primate model restored circulating sDPP4 levels and this increase was associated with restoration of the Th17 cell compartment and reduced inflammation in the gut mucosa (143), thus suggesting that circulating sDPP4 could be used as a surrogate marker for HIV-induced intestinal damage.…”
Section: Paper Imentioning
confidence: 91%